The abacus and the cross: the story of the Pope who brought the light of science to the Dark Ages - Brown, Nancy Marie (Basic Books, 2010)
A monk of Aurillac -- Of the making of books there is no end -- The ornament of the world -- Schoolmaster of Reims -- The abacus -- Math and the mind of God -- The celestial sphere -- The astrolabe -- Abbot of Bobbio -- Treason and excommunication -- The legend of the last emperor -- Pope of the year 1000 -- The end of the world